An Eye Tracking Approach to Understanding Misinformation and Correction Strategies on Social Media: The Mediating Role of Attention and Credibility to Reduce HPV Vaccine Misperceptions. Issue 13 (10th November 2021) - Kim, Sojung Claire; Vraga, Emily K.; Cook, John
ABSTRACT: This study uses an unobtrusive eye tracking approach to examine understudied psychological mechanisms – message attention and credibility – when people are exposed to misinformation and correction on social media. We contrast humor versus non-humor correction strategies that point out rhetorical flaws in misinformation regarding the HPV vaccine, which was selected for its relevance and impact on public health. We randomly assigned participants to one of two experimental conditions: humor correction versus non-humor correction. Our analyses revealed that the humor correction increased attention to the image portion of the correction tweet, and this attention indirectly lowered HPV misperceptions by reducing the credibility of the misinformation tweet. The study also found that the non-humor correction outperformed the humor correction in reducing misperceptions via its higher credibility ratings. Practical implications for correcting misinformation on social media are discussed.